Home before dark : [large type] a novel - Sager, Riley (Thorndike Press large print basic, 2020)
"Bells that ring themselves. Record players that turn on an play music to empty rooms. Ghosts that can climb out of wardrobes... Maggie Holt doesn't believe in these things, even though they are the details of the story that made her family famous. Twenty-five years ago, she and her parents, Ewan and Jess, moved to Baneberry Hall, a rambling Victorian estate in the Vermont woods. They spent twenty days there before fleeing in the dead of night, an ordeal Ewan later recounted in a horror memoir, House of Horrors. His tale of ghostly happenings and encounters with the malevolent spirits became a worldwide phenomenon, rivaling The Amityville Horror in popularity - and skepticism. Maggie has lived her life in the shadow of her father's book, so when she inherits Baneberry Hall after his death, she returns to renovate the house to prepare it for sale. However, her homecoming is anything but warm. People from the past, chronicled in the House of Horrors, lurk in the shadows. And locals aren't thrilled that their small town has been made infamous thanks to Maggie's father. Even more unnerving is Baneberry Hall itself - a place filled with relics from another era that hint at a history of dark deeds. As Maggie experiences strange occurrences straight out of Ewan's book, she starts to wonder if what he wrote was more fact than fiction. Alternating between Maggie's uneasy homecoming and chapters from her father's book, this is the story of a house with long-buried secrets and a woman's quest to uncover them - even if the truth is far more terrifying than any haunting" --Publisher.